Characterization of dissolved organic matter from Australian and Chinese source waters by combined fractionation techniques - Wei, Qunshan (Water science and technology : a journal of the International Association on Water Pollution Research, 2011)
The character of dissolved organic matter (DOM) in source waters from two countries (Australia and China) was investigated using an extended fractionation technique by combining resin adsorption, ultrafiltration and high performance size exclusion chromatography. There are distinctive chemical characteristics associated with DOM origins. Australian sourced DOM had higher hydrophobic acid (HoA) content and exhibited a more pronounced humic character, indicating a higher influence from allochthonous organics (decayed plant bodies from vegetated catchments). The higher content of hydrophobic base and neutral components found in Chinese DOM, may be attributed to the effects of increasing pollution caused by the rapid urbanization in China. The molecular weights (MWs) of aquatic HoA are predominantly in the moderate (e.g., 1-10 kDa) or small (e.g., < 1 kDa) ranges. This suggests that aquatic HOA should not be assumed as high MW organics without experimental validation. It is also found that some of the low MW compounds in our samples were hydrophobic, which could explain the observation of low MW organic compounds being able to be removed by conventional treatment processes